A Review of the Surgical Treatment for Constrictive Pericarditis - Khan, Imran (ARYA atherosclerosis, 2023)
Chronic constrictive pericarditis results in the signs and symptoms of heart failure due to the chronic compression of the myocardium. When the pericardium becomes thickened and fibrosed, surgery is the sole curative management strategy. Surgery leads to an improvement in functional status and survival, but it is associated with significant mortality and morbidity. Over the years, the surgical approach to this pathology has largely remained unchanged, but there has been a shift in the etiological mechanism of constrictive pericarditis from predominantly tuberculous to post-cardiac surgery and idiopathic pathologies. This review offers an overview of the surgical management of constrictive pericarditis.